Consideration Model And Its Influence On The Social Skills Of Children With Emotional And Behavioural Barriers - Nandi Warnandi; Dea Yulida; Neni Satriani; J Juhanaini; S Sunardi (Universitas Pendidikan Indonesia (UPI), 2023)
Children with emotional and behavioural barriers are children who have obstacles to connecting with other people. Conditions in the field showed that children with emotional and behavioural barriers have low social skills. This problem is indicated by behaviour that is not in accordance with applicable rules, norms, and even laws. This research aims to determine the influence of the consideration model on the skills of children with emotional and behavioural barriers. This type of research is experimental. The design used is One Group Pre-Test Post- Test. The sample used in this research consisted of six students. Data collection was carried out using systematic observation instruments regarding social skills. Data analysis used non-parametric statistical techniques with the Wilcoxon test. The conclusion of this research is that the consideration learning model is influential in improving the social skills of children with emotional and behavioural barriers. It is hoped that the consideration model can be used by teachers in learning social skills for children with emotional and behavioural barriers.